Small-signal stability analysis of power systems with high renewable penetration based on dynamic equivalent model - Yong Yan; Bin Wang; Wanwan Xu; Jiang Liu; Ruohan Gong (International Journal of Electrical Power & Energy Systems, 2025)
The penetration of renewable energy into power grids through converters is increasing, and modern power systems are gradually transforming into multi-converter systems. In practical situations, converters are configured with parameters according to different working conditions. Due to differences in control parameters, the dynamics of the converters vary, and as the number of converters increases, this leads to the “curse of dimensionality” problem in modal analysis. The common approach to handle this is to assume that the dynamics of all or adjacent converters are identical, but this can introduce inaccuracies in the results of stability analysis. This paper thoroughly considers the differences among all converters and proposes a novel dynamic equivalent model for multi-converter systems with different dynamics (MCS-DD). In this equivalent model, the discrepancy between the dynamics of the ith converter and the standard converter dynamics is superimposed onto the grid-side node connected to the ith converter in the form of series–parallel dynamic admittance. After equivalence, the dynamic characteristics of all converters become identical to those of the standard converter, thereby reducing the full-order model of n converters from n×m dimensions to 1×m dimensions, while keeping the dimension of the grid-side admittance matrix constant. Modal analysis based on the dynamic equivalent model reduces computational complexity and improves the accuracy of the system stability analysis results. The effectiveness of this method is verified through both modal analysis and time-domain simulation on a two-area four-converter test system and a nine-converter system.